Kinetic Spectrophotometric Determination of Certain Cephalosporins in Pharmaceutical Formulations - Mahmoud A. Omar; Osama H. Abdelmageed; Tamer Z. Attia (International Journal of Analytical Chemistry)
A simple, reliable, and sensitive kinetic spectrophotometric method was developed for determination of eight cephalosporin antibiotics, namely, Cefotaxime sodium, Cephapirin sodium, Cephradine dihydrate, Cephalexin monohydrate, Ceftazidime pentahydrate, Cefazoline sodium, Ceftriaxone sodium, and Cefuroxime sodium. The method depends on oxidation of each of studied drugs with alkaline potassium permanganate. The reaction is followed spectrophotometrically by measuring the rate of change of absorbance at 610 nm. The initial rate and fixed time (at 3 minutes) methods are utilized for construction of calibration graphs to determine the concentration of the studied drugs. The calibration graphs are linear in the concentration ranges 5–15 𝜇g mL−1 and 5–25 𝜇g mL−1 using the initial rate and fixed time methods, respectively. The results are validated statistically and checked through recovery studies. The method has been successfully applied for the determination of the studied cephalosporins in commercial dosage forms. Statistical comparisons of the results with the reference methods show the excellent agreement and indicate no significant difference in accuracy and precision.